Les arbres de Tunis peuvent-ils devenir un patrimoine urbain ? Pour qui ? Pourquoi ? - Myriam Bennour Azooz (Projets de Paysage)
For our case which is Tunis, we’ve been relied on in-situ observations and results of interviews with the citizens to attempt to define; first, the status of the tree of Tunis. Then, second, we do a few assumptions about the perception of the tree by the citizens. We advance the following thesis: the social perception of the tree of Tunis is built on the personal identity of the inhabitants of the city. Nevertheless, the tree helps also to forge the identity of the urban public space by marking their life. The perception of the tree becomes a complex mix of practicality, traditions, religious beliefs and personal experiences.